Cold storage systems for electricity management: Performance analysis in office and power plant applications - Ramin Mehdipour; Behnam Feizollah Beigi; Romina Fathiraboki; Hasan Asgari; Zahra Baniamerian (Next Energy)
In hot seasons, residential areas consume significant amounts of electricity for refrigeration and air conditioning, leading to peak power consumption. This simultaneous increase in cooling load, combined with reduced performance of gas turbines, places considerable stress on the power grid, particularly during specific periods each year. Cold storage systems offer an effective solution by shifting electricity consumption from peak daytime hours to off-peak nighttime periods. This study evaluates and compares the economic and thermal performance of cold storage systems implemented in both power plants and office buildings for peak demand management. Tailored cold storage systems were designed for each application, with a focus on ensuring reliable performance during peak cooling demand based on load analysis. The study utilized real-world case studies, including modeling for an office building in Arak, Iran, and a nearby power plant, to understand the impact of different climatic conditions on system performance. The results indicate that, during peak hours, the turbine’s net power output improved by 15.98% and 17.97% with partial and full storage methods, respectively, compared to scenarios without cooling. Additionally, the economic analysis revealed substantial cost savings, with partial and full storage systems resulting in reductions of 97.36% and 95.54%, respectively, in power plant units compared to similar office buildings with equivalent power consumption. The analysis also highlights that full storage systems in both office and power plant contexts deliver better peak shaving performance but at a higher cost due to the larger size of tanks and equipment required for operation. These findings underscore the potential of cold storage systems as an effective strategy for enhancing electricity management and reducing operational costs.